Thalassioneis signyensis (bacillariophyceae) from northwest weddell sea icebergs, an emendation of the generic description - Ferrario, Martha Elba; Cefarelli, Adrián Oscar; Robison, Bruce; Vernet, María (Journal of Phycology)
We offer an emended description of the genus Thalassioneis based on new observations of the type species, T. signyensis Round, from material sampled in the northwest Weddell Sea. Specimens from algal communities attached to submerged flanks of several icebergs were collected with a remote-operated vehicle (ROV-Phantom DS 2). The analyses were carried out by LM and SEM. Fresh material and frustules without organic matter allowed us to observe details not included in the original description such as type and structure of colonies and chloroplasts. The frustule shows an asymmetry with respect to the location of the apical pore fields, one of them situated on the valvar face and the other one displaced toward the mantle; the former is involved in joining contiguous cells to form long chains. Furthermore, we present details on the ultrastructure of the cingulum that consists of three to four open copulae with one or more rows of poroids. A brief discussion on the habit and ecology of this taxon, which may be endemic to the northwest Weddell Sea, is also presented. A comparison with similar genera, such as Brandinia, Creania, Fossula, Fragilaria, Rimoneis, Synedropsis, and Ulnaria, is included with an evaluation of morphological characteristics useful to differentiate them. Fil: Ferrario, Martha Elba. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Ficología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Cefarelli, Adrián Oscar. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Ficología; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Robison, Bruce. Monterey Bay Aquarium Research Institute; Estados Unidos Fil: Vernet, María. University of California at San Diego; Estados Unidos